2015
DOI: 10.1093/femsle/fnv072
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-like enzyme activities from chlorophycean green algae with potential for bioconversion of phenolic pollutants

Abstract: In order to explore the abundance and potential environmental functions of green algal laccases, we screened various algae for extracellular laccase-like activities, characterized basic features of these activities in selected species and exemplarily studied the transformation of environmental pollutants and complex natural compounds by the laccase of Tetracystis aeria. Oxidation of the classical laccase substrate ABTS was found to be widespread in chlorophycean algae. The oxidation activity detected in member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…There are conflicting reports on exact appearance of LACs in plants. Green unicellular algae, such as Volvox carteri and Chlamydomonas reinhardtii, were suggested to have genes encoding for LACs Zhao et al, 2013) although no LAC enzymatic activities had been detected in these species (Otto et al, 2015).…”
Section: Laccases Distribution Of Laccases Among Kingdoms and Speciesmentioning
confidence: 99%
“…There are conflicting reports on exact appearance of LACs in plants. Green unicellular algae, such as Volvox carteri and Chlamydomonas reinhardtii, were suggested to have genes encoding for LACs Zhao et al, 2013) although no LAC enzymatic activities had been detected in these species (Otto et al, 2015).…”
Section: Laccases Distribution Of Laccases Among Kingdoms and Speciesmentioning
confidence: 99%
“…Kinetic equations, which describe the growth in relation to a nutrient, are important in understanding many phenomena in biotechnological and ecological processes. C. moewusii is a microalga widely used as a model organism for many studies in biology, for example, toxicological studies (Su arez et al 2010, Mera et al 2014, flagellar structure (Jones and Lewin 1960), studies with chloroplasts (Richard et al 1994), biosynthesis of metabolites , biotransformation (Otto et al 2015), and genetic studies (Bussieres et al 1996).…”
mentioning
confidence: 99%
“…Some extracellular enzymes such as protease (Kellam and Walker 1987), phenol oxidase (Otto and Schlosser 2014), and laccase like enzyme (Otto et al 2015) have been identified in some Chlorophyta EPSs. Other exoenzymes were also found in several microalga strains (Liu et al 2016).…”
Section: Protein and Antioxidant Enzymes Analysismentioning
confidence: 99%